2004
DOI: 10.1177/004051750407401107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Fabric Pilling with Light-Projected Image Analysis

Abstract: An innovative method and a device for objectively evaluating fabric pilling grade based on light projection using image analysis is presented in this paper. The method can eliminate interference with pilling information from fabric color and pattern. The device for acquiring light-projected images, detecting the profile of projected images, segmenting pills appearing on converted gray images, extracting of a pill's feature index, and so on are discussed in detail. Pilling grade is assessed by a Kohonen self-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…This process can be done using a digital scanner (Kim & Kang, 2005;Palmer, Joud, & Wang, 2005;Palmer & Wang, 2003;Semnani & Ghayoor, 2009;Yun, Kim, & Park, 2013), a camera (Behera & Mohan, 2005;Hsi, Bresee, & Annis, 1998a;Torres & Navarro, 1998;Xin, Hu, & Yan, 2002), a light projected on camera (Chen & Huang, 2004), a camera attached to a microscope (Izabela, 2009), optical triangulation topographic reconstruction of the fabric surface (De Oliveira Mendes, Fiadeiro, & Miguel, 2010, 2011De Oliveira Mendes, Fiadeiro, Miguel, & Lucas, 2009), a laser line projected on the surface of the fabric specimen (Kang, Cho, & Kim, 2004), or a stereovision surface reconstruction using two CCD cameras (Kang et al, 2004).…”
Section: Fabric's Surface Digitizationmentioning
confidence: 99%
“…This process can be done using a digital scanner (Kim & Kang, 2005;Palmer, Joud, & Wang, 2005;Palmer & Wang, 2003;Semnani & Ghayoor, 2009;Yun, Kim, & Park, 2013), a camera (Behera & Mohan, 2005;Hsi, Bresee, & Annis, 1998a;Torres & Navarro, 1998;Xin, Hu, & Yan, 2002), a light projected on camera (Chen & Huang, 2004), a camera attached to a microscope (Izabela, 2009), optical triangulation topographic reconstruction of the fabric surface (De Oliveira Mendes, Fiadeiro, & Miguel, 2010, 2011De Oliveira Mendes, Fiadeiro, Miguel, & Lucas, 2009), a laser line projected on the surface of the fabric specimen (Kang, Cho, & Kim, 2004), or a stereovision surface reconstruction using two CCD cameras (Kang et al, 2004).…”
Section: Fabric's Surface Digitizationmentioning
confidence: 99%
“…Because of the inconsistency and inaccuracy of rating results obtained with the visual method, more reliable and objective methods for pilling evaluation are desirable for the textile industry. Chen & Huang, 2004 evaluated and graded fabric pilling based on light projection using image analysis and neural network to overcome the common difficulty of interference with fabric pill information from fabric color and pattern. Firstly, they eliminated interference with pilling information from fabric color and pattern.…”
Section: Woven Fabric Defectsmentioning
confidence: 99%
“…The total number of iterations in the training process was 400, and the learning rate was initialized to be 0.02.They concluded that the objective pilling grade was in good agreement with the subjective pilling grade. The correlation coefficient for training and testing samples were reported up to 0.94 and 1 respectively (Chen & Huang, 2004). Beltran et al, 2005 also used artificial neural networks to model the multi-linear relationship between fiber, yarn and fabric properties and their effect on the pilling propensity of pure wool knitted fabrics.…”
Section: Woven Fabric Defectsmentioning
confidence: 99%
“…Further on, the impact permeability has been studied (Tokarska & Gniotek, 2009) and the quality of the neural models has been assessed (Tokarska, 2006). The pilling propensity of the fabrics has been predicted (Beltran et al, 2005) and the pilling of the fabrics has been evaluated (Chen & Huang, 2004;, while the presence of fuzz fibres has been modelled (Ucar & Ertugrul, 2007). The evaluation of the wrinkle of the fabrics has been realized on an objective basis with a system based on ANNs (Su & Xu, 1999;Kim, 1999;Mori & Komiyama, 2002).…”
Section: Fabricsmentioning
confidence: 99%